Profit Sharing System of Oil Palm Fresh Fruit Bunches (FFB) between Plasma Farmers and Palm Oil Companies in Kalimantan Province - Ismawartati Ismawartati; Aktris Nuryanti; Rachmawati Rachmawati; Siti Rohani; Muhammad Qahar Awaka (PT Mattawang Mediatama Solution, 2023)
The aim of this research is tosystem of oil palm fresh fruit bunches (FFB) between plasma farmers and palm oil companies in Kalimantan Province. This research is socio-legal legal research that was carried out at PT. Ichtiar Gusti Pudi in South Amboyo Village, Ngabang Subdistrict, Landak Regency, West Kalimantan Province. Primary legal materials are the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 2014 concerning Plantations and the Civil Code, as well as various regulations related to oil palm plantation activities. Secondary legal materials involved legal books, especially those related to oil palm plantations included various articles and journals related to the problems in the research. Tertiary legal materials are the Law Dictionary and the Big Indonesian Dictionary, both printed and online versions. A data collection tool was in the form of interviews. Interviews were conducted with respondents and resource persons consisting of plasma farmers, managers of PT. Ichtiar Gusti Pudi in South Amboyo Village, Ngabang Subdistrict, Landak Regency, and administrators of the Maju Mandiri Cooperative, as well as Head of the Landak Regency Plantation Service. Data analysis consists of a flow of activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. The urgency of contracts or agreements in the oil palm Fresh Fruit Bunches (FFB) production sharing system between plasma farmers and palm oil companies is required to clarify the rights and obligations of each party, including the oil palm Fresh Fruit Bunches (FFB) profit sharing system between plasma farmers and palm oil plantation companies.